The Perceptions and Expectations Toward the Social Responsibility of Hospitals and Organizational Commitment of Nursing Staff. Issue 3 (September 2016) - Hsieh, Sheng-Che; Chiu, Herng-Chia; Hsieh, Ya-Hui; Ho, Pei-Shen; Chen, Li-Chin; Chang, Wei-Chou
ABSTRACT: Background: The labor rights of medical workers in hospitals in Taiwan have been a key issue of discussion and controversy in recent years. Generally, poor work conditions and manpower shortages in hospitals have resulted in a vicious circle of severely overworked medical and healthcare staff and chronically low staffing and retention rates. Purpose: This study employed corporate social responsibility as the conceptual framework of the social responsibility of hospitals to examine the perceptions and expectations of nurses toward the social responsibility practices of the hospital where they serve and to explore the relationship between these perceptions and organizational commitment (OC). Methods: The participants were all nurses who were employed by one medical group in southern Taiwan. Two hundred forty anonymous questionnaires, which included scales that were designed to measure the social responsibility of hospitals and OC, were distributed. Two hundred twenty-seven valid questionnaires were returned. Exploratory factor analysis was used to validate the dimension of the social responsibility of hospitals, and hierarchical multiregression analyses were used to verify the relationship between the perceptions of nurses with regard to the social responsibility practices of the hospital where nurses serve and OC. Results: There were considerable differences between participants' perceptions and expectations toward the social responsibility of hospitals. The nurses with high perceptions toward the social responsibility practices of the hospital where they serve tended to have relatively high OC. Senior nurses who had high perceptions of the legal and rational, ethical, and economic dimensions of the social responsibility practices of the hospital where they serve exhibited relatively strong affective commitment. Nurses in junior positions who had high perceptions of the practices of ethical responsibilities exhibited relatively strong continuance commitment. Senior nurses who had high perceptions of the legal and rational, ethical, and discretionary dimensions of the social responsibility practices of the hospital where they serve exhibited relatively strong normative commitment. Conclusions/Implications for Practice: A friendly and humane work environment in hospital settings facilitates the implementation of social responsibility, which has been shown to foster higher levels of organizational identification and job performance among nurses and other hospital employees.